PENERAPAN DIR FLOORTIME PADA ANAK DENGAN AUTISM SPECTRUM DISORDER UNTUK MENINGKATKAN KEMAMPUAN SOSIAL - Elita Kirana; Ediasri T Atmodiwirjo; Debora Basaria (Universitas Bunda Mulia, 2018)
ABSTRACT: Children with autism have deficit characteristics in social communication and social interaction, as well as restricted and repetitive patterns of behavior, and limited interests or activities. As children grow and engage in a wider environment, this is become a problem because of the lack of social skills on children with autism. The purpose of this research is to improve the social skills of children with autism. There are several methods that can be applied to children with autism to improve their social skills. One of them is the DIR (Developmental, Individual Differences, & Relationship Based) Floortime method. DIR Floortime aims to help children reach the stage of their emotional development through play activities. This type of research is a clinical case study, involving two middle childhood boys that are diagnosed with a mild level of autism. The instruments used in this study are Autism Social Skills Profile and Functional Emotional Assessment Scale. This research involves 20 sessions, conducted in May until June 2018, consisting of 10 sensory sessions and 10 symbolic sessions for each subject. The results of this research show an improvement in social skills in both participants, marked by an increase in the post test scores, but not significantly. Qualitatively, both subject demonstrates an improvement on social skills in their daily behavior after they had participated in the intervention.Keywords: autism spectrum disorder, middle childhood, DIR Floortime,social skills ABSTRAK: Anak autistik memiliki karakteristik kesulitan dalam komunikasi dan interaksi sosial serta adanya yang minat terbatas, perilaku berulang, atau keterikatan dalam minat dan aktivitas. Hal ini menjadi masalah saat anak tumbuh seiring usia dan terlibat dalam lingkungan yang lebih luas karena kurangnya kemampuan sosial pada anak autistik. Penelitian ini bertujuan untuk meningkatkan kemampuan sosial anak autistik. Ada beberapa metode yang dapat diterapkan pada anak autistik untuk meningkatkan kemampuan sosial. Salah satunya adalah metode DIR (Developmental, Individual Differences, & Relationship Based) Floortime. DIR Floortime bertujuan membantu anak mencapai tahap perkembangan emosionalnya melalui kegiatan bermain. Jenis penelitian ini adalah case study yang melibatkan dua orang partisipan, yaitu anak laki-laki berusia middle childhood dengan autisme level Mild. Instrumen dalam penelitian ini adalah Autism Social Skills Profile dan Functional Emotional Assesment Scale. Penelitian ini berlangsung selama 20 sesi intervensi yang dilaksanakan pada bulan Mei hingga Juni 2018. Sesi intervensi terdiri dari 10 sesi sensori auditori dan 10 sesi simbolik bagi masing-masing subjek. Hasil penelitian menunjukkan adanya peningkatan yang signifikan pada kapasitas emosi, tetapi kemampuan sosial kedua partisipan tidak meningkat secara signifikan. Secara kualitatif, kedua subjek menunjukkan kemampuan sosial yang lebih baik setelah mengikuti sesi intervensi, hal ini tampak dalam perilaku sehari-hari.Kata kunci: autisme, middle childhood, DIR Floortime, kemampuan sosial